2015
DOI: 10.1007/s11999-015-4503-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Zirconium Head on Crosslinked Polyethylene Liner in Total Hip Arthroplasty: A 7- to 12-year In Vivo Comparative Wear Study

Abstract: Background Osteolysis resulting from wear debris production from the bearing surfaces is a major factor limiting long-term survival of hip implants. Oxidized zirconium head on crosslinked polyethylene (XLPE) is a modern bearing coupling. However, midterm in vivo wear data of this coupling are not known. Questions/purposes The purpose of this study was to investigate in vivo whether the combination of an oxidized zirconium femoral head on XLPE produces less wear than a ceramic head on XLPE or a ceramic head on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
1
24
0
1
Order By: Relevance
“…Fifty-eight partially RPPTs from 2005 onwards were found, of which 44 (including 24 873 patients) were eligible for at least basic data extraction (table 1), and 20 could be included in the meta-analyses (PRISMA flow chart, figure 1). 15–72 Exclusion reasons for the meta-analyses were: no availability of both treatment outcomes in the randomised and preference cohorts separately in 14 trials,15 16 18 19 23 24 27 30 31 34 39 41 42 63 no availability of SDs, which could also not be converted from other available data in five trials,21 29 49 52 62 and the number of events or the power of one or both cohort(s) was too low to perform separate randomised and preference analyses in five trials 25 28 40 55 72. The trials covered a wide range of clinical areas and interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-eight partially RPPTs from 2005 onwards were found, of which 44 (including 24 873 patients) were eligible for at least basic data extraction (table 1), and 20 could be included in the meta-analyses (PRISMA flow chart, figure 1). 15–72 Exclusion reasons for the meta-analyses were: no availability of both treatment outcomes in the randomised and preference cohorts separately in 14 trials,15 16 18 19 23 24 27 30 31 34 39 41 42 63 no availability of SDs, which could also not be converted from other available data in five trials,21 29 49 52 62 and the number of events or the power of one or both cohort(s) was too low to perform separate randomised and preference analyses in five trials 25 28 40 55 72. The trials covered a wide range of clinical areas and interventions.…”
Section: Resultsmentioning
confidence: 99%
“…14 With concerns of tribocorrosion and longterm survival, previous studies have shown OxZr to be superior to both MoP and CoP. 9,30 As Kurtz et al 13 and Mendenhall 31 have shown, the cost differentials between CoP and MoP bearings continue to decrease with time and may soon be cost neutral. While the cost to manufacture OxZr and CoP bearings is beyond the scope of this paper, improvements continue to be made with both bearings and costs to manufacture these continue to decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Cup inclinations greater than 45° have been shown to increase the load‐per‐unit‐area on the superior aspect of the polyethylene. Several studies have correlated cup inclinations of more than 45° to increased wear, while other studies have failed to show this correlation . Reasons for this increased variability may be the use of different prostheses, heads and liners between and within these prior studies.…”
Section: Discussionmentioning
confidence: 99%